Influence of ultrasound-assisted osmotic dehydration on the main quality parameters of kiwifruit. (June 2017) - Nowacka, M.; Tylewicz, U.; Romani, S.; Dalla Rosa, M.; Witrowa-Rajchert, D.
Abstract: The aim of this work was to investigate the effect of ultrasound (US) pretreatment, alone and in combination with osmotic dehydration (OD), on texture, color, chlorophyll content, water activity and freezable water content of kiwifruit. Kiwifruit slices were subjected to ultrasonic waves in the bath at a frequency of 35 kHz for 10, 20 and 30 min. Afterwards, the OD was carried out by immersion of samples in 61.5% sucrose solution for pre-established contact period of 0, 10, 20, 30, 60 and 120 min. From the obtained results it was possible to observe that the effect of US, on overall kiwifruit quality parameters, was not proportionally related to the treatment times. US pretreatment alone positively affected the chlorophyll content, when applied for 20 min, while texture parameter was negatively influenced by all the tested US conditions. When combined with OD, US was able to maintain and sometimes improve the kiwifruit characteristics. Industrial relevance: Ultrasound is a pretreatment widely used to improve the mass transfer in osmotic dehydration process. The results of this research have demonstrated that the US treatment applied on kiwifruit slices did not promote the deterioration of the product quality. In fact, it was able to maintain or, in certain treatment times, even to improve some quality parameters (e.g. chlorophyll content) of kiwifruit subjected to osmotic dehydration process. Therefore, the ultrasound treatment shows high potentials to be applied at industrial level to reduce the time of osmotic dehydration and to obtain novel products with high quality. Highlights: Ultrasound treatment has an impact on chemico-physical properties of kiwifruit. The combination of ultrasound and osmotic dehydration on kiwifruit was studied. Combined treatments promoted a better preservation of chlorophyll in kiwifruit. Ultrasound pretreatment alone caused a lowering of kiwifruit firmness.